Faktor - Faktor Yang Mempengaruhi Ibu Dalam Memberikan ASI Eksklusif: Literatur Review - Mutiara Sepjuita Audia; Widia Lestari; Niken Yuniar Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction: Mother's Milk is the best life liquid that is needed by babies which contains various substances that are important for the growth and development of babies and in accordance with their needs. The importance of exclusive breastfeeding for babies is like nutrition in general, breast milk contains components of macro and micro nutrients. Macronutrients are carbohydrates, protein and fat, while micronutrients are vitamins and minerals. Each component of breast milk has its own benefits for the baby's growth. The lack of exclusive breastfeeding can be caused by various conditions, demographic, socioeconomic, and clinical factors greatly determine the continuity of breastfeeding. Objective: To determine the factors that influence mothers in giving exclusive breastfeeding. Methods: The method used in this study is the narrative review method with literature sourced from the Google Scholar and PubMed databases. Results: Of the 7 articles, there are 5 articles that discuss internal factors that influence mothers in giving exclusive breastfeeding. Internal factors that influence mothers in giving exclusive breastfeeding according to the 5 articles reviewed are knowledge, education, occupation, age, attitude and parity. And from 7 articles there are 4 articles that discuss external factors that influence mothers in giving exclusive breastfeeding. External factors that influence mothers in giving exclusive breastfeeding according to the 4 reviewed journals are social culture, family support and support from health workers. Conclusion: Based on the 7 articles presented, it indicates that there are so many factors that trigger mothers not to give exclusive breastfeeding, both internal factors that come from the mother herself and external factors that come from outside the mother herself.